Functional characterization of a U5 ribozyme: intracellular suppression of human immunodeficiency virus type 1 expression. - Dropulić, B (1992)
We have designed a ribozyme that cleaves human immunodeficiency virus type 1 (HIV-1) RNA in U5 (at nucleotide +115). This ribozyme was tested in vitro and was found to give efficient and specific digestion of RNA containing the HIV-1 U5 sequence. When the U5 ribozyme was placed into the HIV-1 genome, virus replication was suppressed in tissue culture. Introduction of this ribozyme into cells by using an amphotropic retrovirus vector significantly reduced expression of U5-containing RNA in cells chronically infected with HIV-1. Naive T cells were cocultivated with packaging cells that produce defective amphotropic retroviruses containing the U5 ribozyme. These lymphocytes were found to be partially protected from HIV-1 infection.